2022
DOI: 10.1177/10436596211072891
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning Research in African Immigrant and Refugee Women: A Scoping Review

Abstract: Introduction: African immigrants are a vulnerable population who are seldom seen in the literature, however, the scant research available reports that they experience increased challenges when making family planning decisions. A robust understanding of their specific family planning practices is imperative to providing appropriate, culturally congruent care. Considering this disparity, a scoping review was conducted to synthesize empirical knowledge and identify gaps in the literature around family planning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The 19 included articles were published between 2013 and 2022, with sample sizes ranging from 10 to 1,773 people (see Table 3 for article characteristics). Thirteen articles reported on qualitative findings (including two mixed-methods studies that only reported on qualitative data) (13/19 articles, 68.4%) [ 40 , 41 ], three quantitative (3/19 articles, 15.8%) [ 42 44 ], one mixed-methods (1/19 articles, 5.3%) [ 45 ], one scoping review (1/19 articles, 5.3%) [ 46 ], and one narrative review (1/19 articles, 5.3%) [ 47 ]. Of the 17 primary articles, four used convenience sampling (4/17 articles, 23.5%) [ 42 , 43 , 45 , 48 ], three used purposive (3/17 articles, 17.6%) [ 40 , 49 , 50 ], four used both purposive and snowball (4/17 articles, 23.5%) [ 51 54 ], two used purposive and convenience (2/17 articles, 11.8%) [ 41 , 55 ], one used informant-purposive and snowball (1/17 articles, 5.9%) [ 56 ], one used convenience and snowball (1/17 articles, 5.9%) [ 57 ], one used purposive, gatekeeper and snowball (1/17 articles, 5.9%) [ 58 ], and one used stratified random sampling (1/17 articles, 5.9%) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 19 included articles were published between 2013 and 2022, with sample sizes ranging from 10 to 1,773 people (see Table 3 for article characteristics). Thirteen articles reported on qualitative findings (including two mixed-methods studies that only reported on qualitative data) (13/19 articles, 68.4%) [ 40 , 41 ], three quantitative (3/19 articles, 15.8%) [ 42 44 ], one mixed-methods (1/19 articles, 5.3%) [ 45 ], one scoping review (1/19 articles, 5.3%) [ 46 ], and one narrative review (1/19 articles, 5.3%) [ 47 ]. Of the 17 primary articles, four used convenience sampling (4/17 articles, 23.5%) [ 42 , 43 , 45 , 48 ], three used purposive (3/17 articles, 17.6%) [ 40 , 49 , 50 ], four used both purposive and snowball (4/17 articles, 23.5%) [ 51 54 ], two used purposive and convenience (2/17 articles, 11.8%) [ 41 , 55 ], one used informant-purposive and snowball (1/17 articles, 5.9%) [ 56 ], one used convenience and snowball (1/17 articles, 5.9%) [ 57 ], one used purposive, gatekeeper and snowball (1/17 articles, 5.9%) [ 58 ], and one used stratified random sampling (1/17 articles, 5.9%) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Women’s countries of origin varied. Seven articles included women from African countries only, including Somalia, Kenya, Sudan, South Sudan, Sierra Leone, Burundi, and Ethiopia (7/19 articles, 36.8%) [ 40 , 46 , 49 , 51 , 52 , 55 , 58 ]. Two articles included women from Syria (2/19 articles, 10.5%) [ 43 , 50 ], two included women from Nepal (2/19 articles, 10.5%) [ 48 , 53 ], one focused on women from Mexico (1/19 articles, 5.3%) [ 47 ], and one included women from mainland China (1/19 articles, 5.3%) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…We will also identify key barriers, facilitators, and social determinants, of postpartum contraception access and utilization in sub-Saharan African immigrant and refugee women. Some of these include, access to insurance coverage, literacy levels, language, patient-provider factors, childcare, transportation, stigma, and knowledge/awareness of available/preferred methods [ 9 , 24 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…African immigrant and refugee populations, specifically populations from sub-Saharan Africa, are rapidly increasing in the United States, and they come from a wide range of cultural, linguistic, religious, and social origins [ 8 ]. Immigrant and refugee populations may have trouble using postpartum contraception and other preventative SRH care because of their prior experiences with SRH in their home countries, and relocation, migration, and resettlement experiences [ 9 ]. Evidence from other high-income migrant-receiving nations in the European Union and Asia [ 10 ], and a recent systematic review of five countries [ 11 ] have revealed many factors that contribute to low rates of maternal health care use among immigrant women.…”
Section: Introductionmentioning
confidence: 99%
“…In many sub-Saharan African countries, contraceptive prevalence rates have plateaued, with access to contraception remaining constrained for many rural, poor, and vulnerable populations. 1 3 The development of new contraceptive methods that better meet users' needs, particularly those in resource-constrained and remote locations, holds the promise of increasing method use and satisfaction. Studies have shown that expanding the method mix and improving features of current methods can lead to increased contraceptive use.…”
Section: Introductionmentioning
confidence: 99%